2022
DOI: 10.3389/fmed.2022.777368
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Radiomics Features of Magnetic Resonance T2-Weighted Imaging Combined With Clinical Characteristics to Predict the Recurrence of Acute Pancreatitis

Abstract: ObjectiveTo explore the diagnostic value of radiomics model based on magnetic resonance T2-weighted imaging for predicting the recurrence of acute pancreatitis.MethodsWe retrospectively collected 190 patients with acute pancreatitis (AP), including 122 patients with initial acute pancreatitis (IAP) and 68 patients with recurrent acute pancreatitis (RAP). At the same time, the clinical characteristics of the two groups were collected. They were randomly divided into training group and validation group in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Chen et al (17) first showed that the radiomics model based on CECT exhibits promising value in the early prediction of RAP. In another similar study, Hu et al (18) constructed a multivariate logistic regression radiomics model, radiomics, and clinical characteristics combined model based on MRI-T2WI, and their results were consistent with those of Chen et al (17).…”
Section: Clinical Applications Predicting Recurrent Acute Pancreatitissupporting
confidence: 71%
“…Chen et al (17) first showed that the radiomics model based on CECT exhibits promising value in the early prediction of RAP. In another similar study, Hu et al (18) constructed a multivariate logistic regression radiomics model, radiomics, and clinical characteristics combined model based on MRI-T2WI, and their results were consistent with those of Chen et al (17).…”
Section: Clinical Applications Predicting Recurrent Acute Pancreatitissupporting
confidence: 71%
“…The fact that texture analysis of the pancreas is an important predictor of AP prognosis confirms its significance in the initial diagnosis of patients with CT indication. Previous studies pointed out the relevance of radiomics analyses in the prediction of AP recurrence [19,34,35]. Furthermore, the prediction of AP severity is of high clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) ≥ 25 kg/m 2 was defined as overweight, and BMI <25 kg/m 2 was defined as not overweight ( Caballero, 2019 ). Patients with a prior history of acute pancreatitis admitted to the hospital for treatment were defined as Recurrent AP ( Hu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%